Impact of coal-fired power station on the community of harpacticoid copepods in estuarine ecosystem at Sarawak river - Agatha, Alfred (Universiti Malaysia Sarawak (UNIMAS), 2005)
The aim ofthis study was to assess the immediate and seasonal impacts of the operation of Coal-Fired Power Plant (CFP) on the community structure of harpacticoid copepods. Two approaches have been taken to conduct the study which involved transect sampling (impact of CFP study) conducted during September 2003 and monthly sampling (seasonal variation study), which was done from March 2003 until February 2004. Total density of harpacticoid copepods obtained from Sarawak River at Muara Tebas ranged from 10 to 245 ind.l10 cm2 (impact of CFP study) and from zero individual to 444 ind.l10 cm2 (seasonal variation study). A total of 92 species has been identified for the impact of CFP study and 111 species from the seasonal variation study. Density and distribution of the dominant species at the study area were considered to determine the characteristic of overall community of harpacticoid copepods species. Dominant species of harpacticoid copepods in overall stations from the impact of CFP study were Enhydrosoma Jongifurcatum and MicroseteJJa rosea. As for the seasonal variation study, Enhydrosoma propinquum and Amphiascopsis sp.3 were found to dominate in the effluent outlet station. Amphiascopsis sp.3 was found to be dominant at the first control station (opposite effluent station). Several physico-chemicals factors such as temperature, chlorine concentration, pH, salinity, dissolved oxygen, total organic matter, chlorophyll a and sediment types have affected the community structure of harpacticoid copepods at the study areas. Impacts of the operation of Coal-Fired Power Plant are considered low and much localized within the vicinity of the effluent outlet. Several species are suggested as a bioindicator of pollution monitoring such as Enhydrosoma Jongifurcatum and MicroseteJJa rosea (on-site impact), and Enhydrosoma propinquum, Amphiascopsis sp.3 and Stenhelia sp.3 (long term pollution monitoring).